2020
DOI: 10.5888/pcd17.200029
|View full text |Cite
|
Sign up to set email alerts
|

Food Swamps Surrounding Schools in Three Areas of Guatemala

Abstract: 200029. PEER REVIEWEDRetail food environment index (RFEI) (1) for 3 neighborhoods of different socioeconomic status in Guatemala: A, Chisec, a rural indigenous community located 4 hours north of Guatemala City; B, a middle-socioeconomic-status urban area of Guatemala City; and C, a high-socioeconomic-status urban area of Guatemala City. RFEI is the ratio of unhealthy to healthy food outlets: the higher the score, the less healthy the food environment. Maps identify stores -corner stores, fastfood outlets, farm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 8 publications
1
15
0
Order By: Relevance
“…Most studies ( n = 39) identified a significant number of establishments selling unhealthy foods around schools. It can be characterized as food swamps, neighborhoods with many unhealthy food establishments, where robust strategies marketers constantly direct and promote this type of food [ 56 , 57 , 65 , 67 ]. As school is the environment where children and adolescents spend most of their day (while they are awake).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies ( n = 39) identified a significant number of establishments selling unhealthy foods around schools. It can be characterized as food swamps, neighborhoods with many unhealthy food establishments, where robust strategies marketers constantly direct and promote this type of food [ 56 , 57 , 65 , 67 ]. As school is the environment where children and adolescents spend most of their day (while they are awake).…”
Section: Resultsmentioning
confidence: 99%
“…The association between the food environment around schools and health-related outcomes was examined by 20 studies [ 2 , 12 , 13 , 14 , 24 , 26 , 40 , 46 , 47 , 49 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 63 , 64 , 65 ], which evaluated the following indicators in children and adolescents: overweight/obesity ( n = 12), body mass index (BMI) ( n = 9), score BMI ( n = 5), BMI percentile ( n = 7), body fat percentage ( n = 6), and fat mass index ( n = 1). Of these, three studies found that schools with the highest number of cafeterias, fast-food restaurants, and food advertisements in the territory had a higher proportion of obese children [ 2 , 12 , 13 , 46 ], and the others did not find significant differences.…”
Section: Resultsmentioning
confidence: 99%
“…These foods are commonly consumed among Guatemala girls. 26,27 Each food item was assigned a score of 0 to 5 depending on frequency of food intake (0 being never/rarely and 5 being 2 or more times per day) so that the JFIM ranged from 0 to 25 (0 being no junk food consumed). Some diet indicators were collected using GSHS 2015 questionnaire such as household food insecurity, frequency of having breakfast, and consumption of fast foods.…”
Section: Data Collectionmentioning
confidence: 99%
“…Food swamps, as opposed to food deserts, have mostly been reported in the Global North as a result of the proliferation of fast foods in low-income communities. The article by Chew et al ( 37 ) is one of the few that have reported on food swamps in the Global South as evidence of the high concentration of fast food outlets in low-income locations around schools. The article demonstrates how food swamps are a global health problem and pose a particular threat of adopting unhealthy food practices in communities.…”
Section: Objective and Themes Of The Collectionmentioning
confidence: 99%